COMPARATIVE ANALYSIS OF NAIVE BAYES ALGORITHM AND C4.5 ALGORITHM IN SELECTING TYPES OF UMKM PRODUCTS IN BBPSDMP KOMINFO MEDAN TRAINING - Alex Siregar; Leni Marlina; Khairul; Muhammad Iqbal; Andysah Putera Utama Siahaan (Bulletin of Engineering Science, Technology and Industry, 2024)
This study compares the accuracy of the Naïve Bayes and C4.5 algorithms in determining the most suitable product types for Micro, Small, and Medium Enterprises (MSMEs) participating in the Digital Entrepreneurship Academy (DEA) training program at BBPSDMP Kominfo Medan. This study uses a dataset from DEA participants between 2021 and 2022. The analysis shows that the C4.5 algorithm has a higher accuracy compared to Naïve Bayes, indicating its better effectiveness in helping MSMEs choose product types. These findings suggest that C4.5 is more suitable for applications that require a high level of accuracy, especially in the context of this study. This study provides valuable insights into the selection of algorithms to support decision making in the MSME sector.